The electrification of the built environment and transport through the utilisation of multi-vector community energy systems - Han, Ming-En (2021)
‘Electrify everything’ is considered an important strategy to achieve the net-zero carbon emission goal by 2050, eliminating carbon emissions if renewable energy technologies produce the electricity supply. The phenomenon, however, places a considerable power demand increase on the distribution networks. To ensure the security of electricity supply, an efficient energy system and energy demand reduction play a critical role. This research, focusing on the residential sector, delivered an electrified community model through domestic heating and road transport electrification. The electricity demands of an electrified community were investigated and then addressed using a designed multi-vector community energy system performing smart management measures. This community energy system could flatten the demand peaks, decrease electricity demand, integrate an electrified heating network, electricity grid and decentralised generation, and was demonstrated in three models.